Right Congenital Diaphragmatic Hernia Associated With Hepatic Pulmonary Fusion: A Case Report - Rachida Laamiri; Samia Belhassen; Amine Ksia; Amina Ben Salem; Nahla Kechiche; Sana Mosbahi; Lassaad Sahnoun; Mongi Mekki; Mohsen Belghith; Abdellatif Nouri (EL-Med-Pub, 2016)
We present a case of male newborn presented with respiratory distress at 21 hours of life. The patient was operated for right congenital diaphragmatic hernia (CDH). Hepatic pulmonary fusion (HPF) was found at surgery.